2022
DOI: 10.3389/fpsyg.2022.891146
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of the Effects of Incidental Vocabulary Learning Through Listening to Songs

Abstract: Most studies have shown that reading is an important source of incidental vocabulary learning, and repeated reading may have a positive effect on learning gains. However, the study of incidental vocabulary learning through listening is still limited, and the immediate and long-term effects on different vocabulary knowledge dimensions are unclear. Furthermore, no empirical studies have been conducted to investigate the association between learning gains and preexisting vocabulary knowledge in listening. This ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…We carefully went through the target words and removed two proper nouns (i.e., Carol and Victor) that were misclassified by AntWordProfiler. For off-list words, we excluded 52 acronyms from the 137 off-list words since these words family as the counting unit because we wanted to follow practices discussed in previous studies on incidental vocabulary learning through listening (e.g., Chen and Teng, 2017;Pavia et al, 2019;Nie et al, 2022). By doing so, the present findings can be comparable across prior studies.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…We carefully went through the target words and removed two proper nouns (i.e., Carol and Victor) that were misclassified by AntWordProfiler. For off-list words, we excluded 52 acronyms from the 137 off-list words since these words family as the counting unit because we wanted to follow practices discussed in previous studies on incidental vocabulary learning through listening (e.g., Chen and Teng, 2017;Pavia et al, 2019;Nie et al, 2022). By doing so, the present findings can be comparable across prior studies.…”
Section: Resultsmentioning
confidence: 61%
“…It is still inconclusive if there is superiority of any one of the counting units. In our study, we employed word family as the counting unit because we wanted to follow practices discussed in previous studies on incidental vocabulary learning through listening (e.g., Chen and Teng, 2017 ; Pavia et al, 2019 ; Nie et al, 2022 ). By doing so, the present findings can be comparable across prior studies.…”
mentioning
confidence: 99%
“…Based on studies findings, Chavangklang, Chavangklang, Thiamhuanok and Sathitdetkunchorn (2019) concluded that the size of an EFL learner's vocabulary is a principal element in promoting his/ her ability to comprehend varied texts. Hence, acquiring a wide range of vocabulary contributes to fostering EFL learners' linguistic proficiency levels (Nie, Fu, Rehman & Zaigham, 2022).…”
Section: Definitions and Importance Of Vocabularymentioning
confidence: 99%
“…It was, also, suggested to conduct further studies investigating the impact of the working memory strategy on EFL learners' speaking ability. Nie, Fu, Rehman and Zaigham (2022) explored the effect of listening to songs on Chinese EFL first year university students' ISSN 1110-2721 incidental acquisition of vocabulary. Participants were 140 students, and they were divided into a control group and three experimental groups.…”
Section: Chavangklangmentioning
confidence: 99%